Association between the city region and traumatic dental injuries among adolescents from Santa Maria, South Brazil - Letícia Donato COMIM; Ângela DALLA NORA; Jessica Klöckner KNORST; Débora Nunes de Oliveira RACKI; Júlio Eduardo do Amaral ZENKNER; Luana Severo ALVES (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract This study investigated the association between the city region and traumatic dental injury (TDI) among adolescents from Santa Maria, Rio Grande do Sul, Brazil. A population-based cross-sectional survey was conducted from March to November 2018, which included a representative sample of adolescents (15-19-year-old) attending public and private high schools. A questionnaire on sociodemographic information was sent to the parents/legal guardians of the selected adolescents. TDI in the upper and lower permanent incisors and canines was recorded based on the O'Brien classification. Environmental variables (sociodemographic and structural characteristics of the neighborhoods) were obtained from official publications. Multilevel Poisson regression models were used, and prevalence ratios (PR) and 95% confidence intervals (CI) were calculated. A total of 1,146 adolescents participated in this study. The overall prevalence of TDI was 17.3%, mild trauma was 12.7%, and severe trauma was 5.8%. Adolescents living in the southern region had a prevalence of TDI of 25.3%, compared with 13.6% in the northern region. After adjusting for important cofactors, adolescents living in the southern region were more likely to have TDI than their counterparts in the northern region (PR, 1.91; 95%CI: 1.18-3.11; p = 0.009). Analyzing the number of environmental risk indicators in different regions, the southern region presented a higher mean and median than all other regions. In conclusion, living in the southern region was associated with a higher prevalence and severity of TDI among adolescents from Santa Maria, southern Brazil. Our findings suggest the role of the environment in the epidemiology of TDI.